Necrotizing Soft Tissue Infection with Compartment Syndrome: A Case Report - Yekta Özkılıç; Kaan Gürbüz; Zeynep Türe; Ilhami Çelik (Erciyes Medical Journal, 2019)
Necrotizing soft tissue infection (NSTI) is a rare infectious condition that spreads rapidly and may be associated with compartment syndrome. Group A β-hemolytic streptococcus is one of the most common causative organism of NSTI. Herein, we present a case of NSTI associated with compartment syndrome of the upper extremities following possible tonsillitis. The case was successfully treated after administering systemic antibiotics and performing emergency surgical debridement.